Keanekaragaman Jenis Serangga Di Berbagai Tipe Lahan Sawah - Anna Sari Siregar; Darma Bakti; Fatimah Zahara (Jurnal Agroekoteknologi, 2014)
The objective of this research was to study the diversity of insects on corn, snake and rice and toknow the kind of insect diversity in various type of farms rice field. This research was conductid atKampung Susuk dan Pest Laboratory Faculty of Agriculture, University of North Sumatra, Medan,started in January 2014 until Februari 2014. This research used 3 kinds of traps insect (Sweep Net,Pitfall Trap, Light Trap).The result of research showed that each insect caught consisted of 6 Ordoand16 families in corn with the highest relative density values was 7,69% and the lowest was4,61%, the highest relative density values in rice is 20,8 % and the lowest was 12,5%, the highestrelative density values in snake was 12.1% and the lowest was 9,75%. Shanon-Weiner (H’) indexdiversity value of insect in corn was 2,368 (medium), in rice was 1,822(medium) and in snake was2,258 (medium).Keywords :Diversity, Insect, Farm Type Rice Field